Development and experimental validation of a patient‐specific lumbar spine FE model to predict the effects of instrumentations. Issue 1 (25th October 2016) - Beckmann, Agnes; Mundt, Marion; Herren, Christian; Siewe, Jan; Kobbe, Philipp; Sobottke, Rolf; Stoffel, Marcus; Markert, Bernd
Abstract: A lumbar spine model without instrumentations was created using CT data and validated with experimental results of the same specimen. The specimen was loaded with pure moments in a spine test rig. The material parameters were taken from literature and adapted for better simulation of the experiments. The results show that further calibration of the material parameters and the implementation of additional ligamentous structures are necessary to simulate the spine's motion reliably. (© 2016 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)